Peningkatan Produktivitas Pengolahan Jahe di Desa Tambang melalui Inovasi Mesin Penggiris - Wawan Trisnadi Putra; Jamilah Karaman; Salman Al Farisi; Rangga Ardana Saputra; Reza Kenia Ariestya Pasha; Alfian Fathur Rohim; Ruli Rohmanto; Septa Nugraha; Prisko Wahyu Trinada (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2025)
Ginger processing in Tambang Village Pudak Ponorogo Regency is still low due to the accumulation of harvested ginger, which on average per house can produce 200 kg of raw ginger. ginger to increase the selling value by utilizing technology. To overcome this problem, the method used is to innovate slicing raw ginger into dry ginger by slicing and drying. This research aims to increase the efficiency of ginger processing through innovative ginger slicing machines. The results of the research show that the machine of ginger slicer is able to increase the efficiency of chopping time by 60 Kg/hour and can produce uniform ginger slices in accordance with market standards. This innovation has had a significant impact on increasing the income and welfare of the people of Tambang Village.